¿Se respeta el derecho constitucional de igualdad ante la ley en la regulación sobre medidas cautelares en el arbitraje en contrataciones con el Estado? - Eto Bardales, Gerardo (2024)
Arbitration is an alternative dispute resolution method that is of special relevance in our country given its mandatory nature in disputes arising from contracts signed with the State. In this context, the purpose of this paper is to analyze the regulatory modification regulated by the famous Emergency Decree No. 20-2020, which requires the presentation of a counter-security with a pre-established quantification only for private parties when they request precautionary measures against the State. In this order of ideas, the principle of equality as a guiding principle of arbitration will be analyzed and whether it has been violated by the rule under analysis. After the study carried out, it is concluded that there is a mistaken perception of the State as a weak party in arbitrations and that article 8.2. of the Arbitration Law, which requires a counter-security for an amount not less than the performance guarantee only for private parties to request precautionary measures against the State in arbitrations on public contracts, collides with the right to equality before the law. Finally, a regulatory amendment is proposed in accordance with the principle of reasonableness in the amount required; as well as the possibility for arbitration courts to exercise diffuse control when in each specific case they notice that the principle of equality in access to justice, effective jurisdictional protection and the principle of reasonableness are being violated by imposing an unreasonable amount on the surety bond required as a counter-security.